2020
DOI: 10.1029/2020ms002102
|View full text |Cite
|
Sign up to set email alerts
|

Mean Climate and Tropical Rainfall Variability in Aquaplanet Simulations Using the Model for Prediction Across Scales‐Atmosphere

Abstract: Aquaplanet experiments are important tools for understanding and improving physical processes simulated by global models; yet, previous aquaplanet experiments largely differ in their representation of subseasonal tropical rainfall variability. This study presents results from aquaplanet experiments produced with the Model for Prediction Across Scales-Atmosphere (MPAS-A)-a community model specifically designed to study weather and climate in a common framework. The mean climate and tropical rainfall variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(39 citation statements)
references
References 114 publications
4
32
1
Order By: Relevance
“…Nevertheless, the fact that even the 120‐km MPAS simulated Kelvin waves supports Rios‐Berrios et al. (2020), who demonstrated that MPAS‐A is a “Kelvin‐wave friendly” model in that the model develops robust Kelvin waves regardless of the choice of cumulus or other physical parameterization schemes.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Nevertheless, the fact that even the 120‐km MPAS simulated Kelvin waves supports Rios‐Berrios et al. (2020), who demonstrated that MPAS‐A is a “Kelvin‐wave friendly” model in that the model develops robust Kelvin waves regardless of the choice of cumulus or other physical parameterization schemes.…”
Section: Resultssupporting
confidence: 51%
“…In the simulations with parameterized convection, the wave amplitude is smaller than in the observations, and the wave packets are less distinct (Figures 4c-4e). Nevertheless, the fact that even the 120-km MPAS simulated Kelvin waves supports Rios-Berrios et al (2020), who demonstrated that MPAS-A is a "Kelvin-wave friendly" model in that the model develops robust Kelvin waves regardless of the choice of cumulus or other physical parameterization schemes.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…(2020a); Rios‐Berrios et al. (2020b), used uniform cell spacing of 120, 30, and 15 km everywhere. The fourth experiment is the first of its kind, employing a variable‐resolution mesh with 3 km cell spacing between 20°S and 20°N gradually transitioning to 15 km cell spacing poleward of 30°S and 30°N.…”
Section: Methodsmentioning
confidence: 99%